Developing Learning Media Using Active Presenter for Eleventh-Grade Students of SMK Negeri 1 Bangli - Hitasthana, Made Satya; Putra, I Nyoman Adi Jaya; Pratiwi, Ni Putu Astiti (Universitas Pendidikan Ganesha, 2021)
This research aimed to develop learning media in form of video using screencast application named Active Presenter to help students learned English during COVID-19 and to increase their vocabulary skill. In developing the learning media, Design and Development (D&D) method proposed by Richey and Klein (2007) was applied in this research. There were three instruments used to collect the data, they were interview guide, questionnaire, and expert judgment. The subject of this research was students from SMK Negeri 1 Bangli in Bangli regency North Bali. The result showed that the learning media was highly relevant to the eleven criteria of a good learning media in form of video and was also categorized as a good media. Thus, the learning media in form of video was an essential media to be used to help students learned during COVID-19 as well as to increase vocabulary skill.